Interactive Learning Media Wordwall to Improve Motivation and Geography Learning Outcomes - Diyah Wahyu Setyoningtyas; Nurhadji Nugraha (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
This study examines the application of interactive learning media Wordwall to improve motivation and geography learning outcomes in grade XI-9 students of SMA Negeri 1 Barat, Magetan Regency. Using the Classroom Action Research (CAR) method of the Kemmis and McTaggart model, the study was conducted in three stages: pre-cycle, cycle I, and cycle II. The results showed an increase in learning motivation from 39.72% (pre-cycle) to 57.91% (cycle I) and 80.69% (cycle II). Student learning outcomes also increased with classical completeness from 58.33% (pre-cycle) to 69.44% (cycle I) and 83.33% (cycle II). The application of Wordwall successfully changed the learning paradigm from